2020
DOI: 10.1111/jdv.16273
|View full text |Cite
|
Sign up to set email alerts
|

The role of the interleukin‐23/Th17 pathway in cardiometabolic comorbidity associated with psoriasis

Abstract: Alterations in the innate and adaptive immunity underpin psoriasis pathophysiology, with the Th17 cells subset now recognized as the fundamental cells in the key controlling pathway involved in its pathogenesis. Since psoriasis is a systemic disease with important comorbidity, further knowledge on the interleukin (IL)-23/Th17 axis led to the hypothesis that there may be shared pathogenic pathways between primary skin disease and comorbidity. Psoriasis has been identified as a risk factor for cardiovascular and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 128 publications
(333 reference statements)
1
61
0
4
Order By: Relevance
“…In the course of Ps, increased triglycerides, LDL cholesterol and decreased HDL cholesterol values are the most frequently observed lipid disturbances [1,2]. In our study, the levels of total CHOL and TG as well as CHOL/HDL and TG/HDL ratios were significantly higher in Ps patients than in HVs, while LDL-CHOL did not differ between both groups.…”
Section: Discussionsupporting
confidence: 45%
“…In the course of Ps, increased triglycerides, LDL cholesterol and decreased HDL cholesterol values are the most frequently observed lipid disturbances [1,2]. In our study, the levels of total CHOL and TG as well as CHOL/HDL and TG/HDL ratios were significantly higher in Ps patients than in HVs, while LDL-CHOL did not differ between both groups.…”
Section: Discussionsupporting
confidence: 45%
“…On the other hand, some authors described that the risk of psoriasis being increased in the obese population, and this clinical scenario may negatively affect systemic treatment of psoriasis [21].…”
Section: Obesity and Metsmentioning
confidence: 99%
“…Recent studies revealed that metabolic disorders, including abdominal obesity and serum dyslipidemia, were positively correlated with psoriasis risk 9 , 10 due to their “low-grade chronic inflammatory state” involving the IL-23/Th17 axis 6 . Psoriasis has been identified as a risk factor for metabolic diseases 6 , and increasing evidence provides support for this epidemiological observation. For example, increased IL-23 and IL-17 levels were found in diabetes, suggesting their synergistic role in β-cell damage 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence indicates that TNF-α and IL-1β facilitate insulin resistance development by elevating blood insulin and HDL cholesterol levels 3 and insulin resistance suppresses keratinocyte differentiation, resulting in persistent proliferation 4 . Moreover, the IL-23/Th17 axis has the diabetogenic potential 5 , and psoriasis has been identified as a risk factor for metabolic diseases due to shared pathogenic pathways, including the IL-23/Th17 axis 6 - 8 .…”
Section: Introductionmentioning
confidence: 99%